Discussion Starters: Speaking Fluency Activities for Advanced ESL/ EFL Students - Folse, Keith S. (Michigan : The University of Michigan Press, 1996)
Trata de actividades de interacción oral que promueven la fluidez en el habla para estudiantes avanzados de inglés como segundo idioma.
1. Smoking or nonsmoking 2. Proverbs and values
incluye índice
Col. Educ
Keywords: 1. GUN CONTROL 2. DRINKING AND DRIVING